Individual Differences in Notetaking, Summarization, and Learning from Lectures - Hadwin, Allyson Fiona; Kirby, John R.; Woodhouse, Rosamund A. (Alberta Journal of Educational Research, 1999)
This study investigated working memory, verbal ability, and prior knowledge as predictors of the quality of: (a) students' notes taken during a lecture; (b) summaries of the lecture written during a review period; and (c) recall of the lecture content. The usefulness of taking notes was considered in terms of quality of summarization and recall of the lecture material for three groups of students who: (a) listened to the lecture, took notes, and reviewed those notes; (b) listened to the lecture and reviewed a set of provided notes; or (c) listened to the lecture, took notes, and then reviewed a set of provided notes. Results indicated that students with higher working memory benefit more from listening to the lecture than listening and taking notes. However, the quality of summaries written was a more powerful predictor of performance than the individual differences students' brought to the task. This study extends previous studies by integrating summarization and lecture learning research and providing new insight into the role of notetaking and its relationship to working memory.